Mysore Representative Assembly (1881-1950) - Sreedhara . H, Dr. (IJRDO-Journal of Applied Science, 2015)
An attempt is made in this paper to trace the Mysore Representative Assembly 1881- 1950. In 1853 Dewan C Rangacharlu became Dewan of princely Mysore. He was an able administrator during his administration he made the great achievements. Among the important progressive reforms of those days, the establishment of “ People Representative Assembly” was significant. It helped the people in the administration. It was started on the advise of J.D.Gardon. In 1881 immediately after Dasara Celebration, the Assembly of this was convened at Mysore. In the first session 144 members were presented. From that day on words for the first time in India, the seeds of Democracy were sown in Mysore. The credit of this should go to the king Chamaraja Wodeyar and Dewan Rangacharlu besides Resident Gardon.